Compared activity of agonist molecules towards ecdysone receptor in insect cell-based screening system - Pinto, Ciro Pedro Guidotti [UNESP]; Rickes, Letícia Neutzling; Zotti, Moisés João; Grutzmacher, Anderson Dionei (Instituto Biológico, 2019)
The ecdysone receptor, naturally activated by steroidal hormones, is a key protein for molting and reproduction processes of insects. Artificial activation of such receptor by specific pesticides induces an anomalous process of ecdysis, causing death of insects by desiccation and starvation. In this paper, we established a protocol for screening agonistic molecules towards ecdysone receptor of insect cells line S2 (Diptera) and Sf9 (Lepidoptera), transfected with the reporter plasmid ere.b.act.luc. Therefore, we set dose-response curves with the ecdysteroid 20-hydroxyecdysone, the phytoecdysteroid ponasterone-A, and tebufenozide, a pesticide belonging to the class of diacylhydrazines. In both cell lines, the median effective concentration values on reporter gene induction (EC50) of ponasterone-A was the smallest, meaning the most active agonist molecule. In Sf9 cells, tebufenozide had as smaller EC50 than 20-hydroxyecdysone, indicating the high agonistic capability and lepidopteran specificity. The protocol established in this study can be useful for a quick screening and rational research of site-specific pesticides.

O receptor de ecdisona, naturalmente ativado por hormônios esteroidais, é uma proteína-chave nos processos de muda e reprodução de insetos. A ativação artificial desse receptor por meio de pesticidas específicos induz um processo de ecdise anômala, levando o inseto à morte por dessecação e inanição. Neste trabalho, foi estabelecido um protocolo para a triagem de moléculas agonistas em relação ao receptor de ecdisona nas linhagens celulares responsivas S2 (Diptera) e Sf9 (Lepidoptera), transfectadas com o plasmídeo repórter ere.b.act.luc. Para tanto, curvas de dose-resposta foram estabelecidas com o ecdisteroide 20-hidroxiecdisona, o fitoecdisteroide ponasterona-A e tebufenozida, um pesticida pertencente à classe das diacilhidrazinas. Em ambas linhagens celulares, os valores médios de concentração efetiva para indução gênica (EC50) ponasterona-A foram menores, significando que este é o agonista mais potente. Em células Sf9, a tebufenozida apresentou EC50 menor que a 20-hidroxiecdisona, indicando uma alta atividade agonista e especificidade deste inseticida a lepidópteros. O protocolo estabelecido neste trabalho pode ser utilizado para uma rápida triagem e busca racional de pesticidas de alvo bioquímico específico.
Comparação da atividade de moléculas agonistas em relação ao receptor de ecdisona em um sistema de triagem baseado em linhagens celulares de insetos
Keywords: plasmid; tebufenozide; 20-hydroxyecdysone; ponasterone-A; plasmídeo; tebufenozida; 20-hidroxiecdisona; ponasterona-A